2010
DOI: 10.1111/j.1469-7610.2010.02235.x
|View full text |Cite
|
Sign up to set email alerts
|

Research in people with psychosis risk syndrome: a review of the current evidence and future directions

Abstract: After decades of research, schizophrenia and related psychotic disorders are still among the most debilitating disorders in medicine. The chronic illness course in most individuals, greater treatment responsiveness during the first episode, progressive grey matter decline during early disease stages, and retrospective accounts of "prodromal" or early illness signs and symptoms formed the basis for research on the psychosis risk syndrome,, known variably as "clinical high risk"(CHR), or "ultra-high risk" (UHR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 175 publications
(144 citation statements)
references
References 327 publications
3
134
2
4
Order By: Relevance
“…The authors found a greater BOLD response in patients in the primary sensory-discriminative pain processing region (S1) compared to controls, and noticed reduced activity in the posterior cingulate cortex, insula and brain stem, suggesting abnormal central processing during painful stimuli. Taken together, these findings suggest decreased pain sensitivity as a potential endophenotype of schizophrenia, which may be relevant to enhance diagnostic precision in general, or predictive validity during the ultra-high risk syndrome for psychosis [9]. Furthermore, studies should investigate if symptomatic response to antipsychotic treatment is related to a normalization of pain sensitivity and/or if baseline values could be predictive of future symptomatic response.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a greater BOLD response in patients in the primary sensory-discriminative pain processing region (S1) compared to controls, and noticed reduced activity in the posterior cingulate cortex, insula and brain stem, suggesting abnormal central processing during painful stimuli. Taken together, these findings suggest decreased pain sensitivity as a potential endophenotype of schizophrenia, which may be relevant to enhance diagnostic precision in general, or predictive validity during the ultra-high risk syndrome for psychosis [9]. Furthermore, studies should investigate if symptomatic response to antipsychotic treatment is related to a normalization of pain sensitivity and/or if baseline values could be predictive of future symptomatic response.…”
Section: Discussionmentioning
confidence: 99%
“…Symptom frequency is rated as 1 = infrequent, 2 = recurrent, 3 = very frequent, or 4 = static lifetime or character trait. Consistent with conventions used for the psychotic prodrome, 25 symptoms were included in the analysis if they were of at least moderate severity and were not considered a character trait, unless the severity had increased by at least one point before the onset of the disorder. Regarding onset pattern, the prodrome was classified as acute (o 1 month in duration), subacute (1-12 months in duration), or insidious (4 1 year in duration).…”
Section: Assessment Instrumentsmentioning
confidence: 99%
“…A prodromal period is a period of functional decline in individuals (i.e., social withdrawal, fluctuations in thinking, avolition, etc.) preceding more severe symptoms (i.e., acute psychosis) such as hallucinations and delusions that the DUP figure captures (Correll, et al, 2010). During the search in the literature, little evidence showed researchers considered this phase into their calculations of average delay in treatment.…”
Section: How Are Delays Measured?mentioning
confidence: 99%
“…At the level of the individual are educational, social, and vocational opportunities that can be cut short because of the illness's debilitating effects. Numerous qualitative studies in the literature reveal such costs as key themes when researching individuals (Bay et al, 2016;Connor et al, 2016;Correll, C. U. et al, 2010;Melton & Blajeski, 2017). The same researchers hypothesize that early intervention can reduce and even eliminate these costs if treatment is given early enough.…”
Section: Why Resolving Delays Is Importantmentioning
confidence: 99%
See 1 more Smart Citation